Impact of Carbon Porosity on the Performance of Cathode Microporous Layers in Proton Exchange Membrane Fuel Cells. Issue 2 (9th March 2020) - Govindarajan, R.; Payoyo, J.; Fang, B.; Bonakdarpour, A.; Wilkinson, D. P.
Abstract: Acetylene black carbons were activated under flowing CO2 atmosphere at 900 °C for different treatment times. The impact of this heat treatment on the porosity, hydrophilicity, and surface oxygen groups was carefully examined. Longer periods of activation led to increases in the surface area and porosity of the samples. Pore size distributions of the samples showed an increase in micropores, followed by a rise in mesopores, which indicated the occurrence of pore widening with a longer activation period. When used as a microporous layer for H2 /air fuel cells, samples with higher levels of porosity showed, in general, reduced mass transport performance due to the formation of pooling locations for water. These results highlight the importance of textural pores in carbon structures on the water management in hydrogen fuel cell when operating under high humidity conditions.